Interleukin-17A Exacerbates Ferric Chloride-Induced Arterial Thrombosis in Rat Carotid Artery - Francesco Maione; Antonio Parisi; Elisabetta Caiazzo; Silvana Morello; Fulvio D'Acquisto; Nicola Mascolo; Carla Cicala (International Journal of Inflammation)
Interleukin-17A (IL-17A), the most widely studied member of the IL-17 cytokine family, is a cytokine which emerged to be critical for host defense as well as in the pathogenesis of autoimmune disorders. Moreover, IL-17A is involved in the pathogenesis of cardiovascular diseases, such as atherosclerosis and acute coronary syndrome and in the cardiovascular risk associated with systemic immunological disorders. Consistent with this, we have recently shown that IL-17A increases human and murine platelet response to ADP. In this study we expanded our previous observation and we describe for the first time an in vivo prothrombotic effect of the cytokine. Our results show that IL-17A is synergic with a low FeCl3 concentration in inducing carotid thrombus in rats and suggest that the effect is likely related to a downregulation of CD39 vascular expression and hydrolyzing activity. Our findings indicate that IL-17A might be an important molecule at the interface between hemostasis and inflammation.